Mature Tiankengs are biodiversity hotspots of soil microorganisms in the karst region - Junbo Yang; Xiaohui Wang; Keyi Wang; Danjuan Zeng; Ling Mo; Shuai Li; Baozhu Fang; Bhagwan Rekadwad; Wenjun Li; Gaozhong Pu (Ecological Indicators)
Mature Tiankeng, the negative geological landform surrounded by integral walls as refugia in Karst regions, conserves the unique plant species of karst regions due to isolation from human disturbances and different local microclimates. However, studies exploring the soil biodiversity of mature Tiankengs are lacking entirely. Soil samples were taken from four mature Tiankengs in southwest China, and the species diversity and functions of bacteria and fungi were determined. Generally, the soil nutrient contents, species diversity, and unique species richness of bacteria and fungi were higher in the Tiankeng than in the outside. The microbial functions of human pathogenic, aromatic compounds and plastic degradation associated were higher in Tiankeng than in the outside. Compare to the outside, more bacterial and fungal species in Tiankeng assembled more network modules as well as microbial functions. Results suggested that compared with the outside, rich soil nutrients may contribute the higher microbial diversity and function formed in mature Tiankengs. Since the soil microbial hotspot was defined as soil with small volume and high process rates, we suggest that the theory of soil microbial hotspot may be applied on landscape scales. That is, mature Tiankengs may be treated as the soil microbial hotspots in karst region based on its small volume proportion but high soil nutrients, microbial diversity, and functions. We further suggest identifying the soil microbial hotspots in other landscapes, and this may be key to biological conservation and ecosystem stability with global changes.